2014
DOI: 10.2147/dddt.s64261
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of oxycodone and acetaminophen following single-dose administration of MNK-795, a dual-layer biphasic IR/ER combination formulation, under fed and fasted conditions

Abstract: BackgroundXARTEMIS™ XR (formerly MNK-795) is a combination oxycodone (OC) and acetaminophen (APAP) analgesic with both immediate-release and extended-release (ER) components (ER OC/APAP). The tablets are designed with gastric-retentive ER oral delivery technology that releases the ER component at a controlled rate in the upper gastrointestinal tract. Because consumption of food has demonstrated an impact on the pharmacokinetics (PK) of some marketed products using gastric-retentive ER oral delivery technology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In the primary PK analysis of this study, food intake delayed time to maximum concentration ( t max ) by 1.5 hours and 2 hours, respectively, for OC and APAP, and time to first measurable concentration ( t lag ) by 15 minutes for both. 10 This supports the finding in the present population PK analysis that food decreases the K a of OC and APAP. However, administration of IR/ER OC/APAP with food had no effect on the extent of drug exposure because the area under the concentration vs time curve for OC and APAP remained bioequivalent under high-fat and low-fat fed conditions in the primary PK analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the primary PK analysis of this study, food intake delayed time to maximum concentration ( t max ) by 1.5 hours and 2 hours, respectively, for OC and APAP, and time to first measurable concentration ( t lag ) by 15 minutes for both. 10 This supports the finding in the present population PK analysis that food decreases the K a of OC and APAP. However, administration of IR/ER OC/APAP with food had no effect on the extent of drug exposure because the area under the concentration vs time curve for OC and APAP remained bioequivalent under high-fat and low-fat fed conditions in the primary PK analysis.…”
Section: Discussionsupporting
confidence: 91%
“…8 , 9 However, no clinically meaningful food effects were associated with the use of this gastroretentive technology in a previous study of IR/ER OC/APAP. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 19 27 In PK studies of low-dose combination opioids enrolling healthy adult volunteers, a discontinuation rate of 20%–40% due to vomiting is typical. 21 , 28 , 29 In acute pain studies, short-term multidose regimens of IR HB/APAP and/or IR OC/APAP have reported nausea and vomiting in 14%–42% and 4%–24% of patients, respectively. 19 , 22 , 26 , 27 Similar results have been observed with opioid/ibuprofen and tramadol/APAP combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the recovery obtained with the selected method was higher than others that use shorter concentration intervals [1,18,22]; UPLC-MS/MS methods with simple protein precipitation with acetonitrile [23] or larger volumes of plasma samples [11,19,21,22]; or at least two-step liquid-liquid extraction and evaporation [10,18,22,24]. Other of the advantages of this method is that it allows a high recovery of the analyte from the biological matrix (>99%) and allows multiple samples to be processed in a short period of time.…”
Section: Recovery and Llqmentioning
confidence: 92%